Dermoscopic features and algorithm: A guide to detecting premalignant facial pigmented skin lesions - Chaudhry, Zaeema Sohail; Ghias, Aisha; Nusrat, Wajeeha; Shaheen, Eema; Khan, Zafar Ullah; Rana, Mahwash (Journal of Pakistan Association of Dermatologists, 2023)
Introduction: Detection of pre malignant facial pigmented lesions on a photo damaged ethnic skin has been crucial for dermatologists in preventing malignant transformation. Four types of Facial Pigmented Skin Lesions (FPSLs) render a diagnostic challenge, pigmented actinic keratosis (PAK), early seborrheic keratosis (SK), solar lentigo (SL) and lentigo maligna (LM). Dermatoscopy or epiluminescence microscopy, is skin surface microscopy that has demonstrated to be a non-invasive, in vivo, high yield technique to evaluate a pigmented macule for an atypical evolution. Objective: To establish dermatoscopic findings of clinically challenging FPSLs corresponding to each of PAK, SK, SL and LM and derive an Algorithm to guide in diagnostic features for detecting Premalignant FPSLs. Subjects and Methods: We here in conducted a largest case study a cross sectional analysis of clinically challenging 182 flat FPSLs, evaluated dermoscopic images corresponding to each of pigmented AK, early SK, SL and LM and subsequently biopsied for histopathological evidence. Four major dermoscopic features were evaluated: pigment pattern, sharp demarcation, vascular pattern and follicular/epidermal pattern. Study Design: Cross sectional validation-study Setting: Department of Dermatology Unit II, King Edward Medical University, Mayo Hospital Lahore. Study was carried out over a period of six months from 01-01-2022 to 30-06-2022. Result: We derived an algorithm as a guide in diagnostic features of FPSLs. Pigmented AK on dermoscopy has strawberry pattern in 42% of lesions (background erythema and red pseudo-network, associated with prominent follicular openings surrounded by a white halo), while Sharp demarcation (57.15%) and follicular/epidermal pattern (cerebriform pattern 100% of lesions, milia-like cysts, 50%, and comedo-like openings 38.57%) are characteristic of SK. In SL, homogenous structureless pigmentation is significant entirely (100%). However, in LM predominates pseudonetwork (89.47%), homogenous structureless pigmentation (78%) and vascular patterns while strawberry pattern is observed in (26.31%) of lesions. Conclusion: We developed an â€œAlgorithmâ€ to be used as a guide in diagnostic features of â€œFacial Pigmented Skin Lesions on Dermoscopy,â€ that would aid in early corrective detection. Sharp demarcation with cribriform pattern is characteristic of Sebhorric Keratosis (SK), while homogenous structureless pigmentation without prominent vascular pattern is characteristic of Solar Lentigo (SL). Pigmented Actinic Keratosis (AK) is characterized by prominent strawberry pattern. On the other hand, homogenous structureless pigmentation and vascular pattern with pseudonetwork are featured in Lentigo Maligna (LM), lacking of prominent strawberry pattern. key words: Facial Pigmented Skin Lesions (FPSL), Seborrheic keratosis, actinic keratosis, nevus, lentigo maligna, solar lentigo